Let ants find them: Using ants as eDNA samplers for detecting the invasive spotted lanternfly - Wei-Jiun Lin; Fang-Ling Chloe Liu; Lucie Cho; Chin-Cheng Scotty Yang (NeoBiota)
Environmental DNA (eDNA) has emerged as a valuable tool for detecting invasive species, yet its application in terrestrial ecosystems remains challenging due to uneven eDNA distribution. Ants, which forage and consume carbohydrate-rich honeydew from sap-feeding insects, may serve as effective “biological samplers” for invasive species detection. In this study, we evaluated whether ants could facilitate eDNA-based detection of the invasive spotted lanternfly (Lycorma delicatula, SLF), given this invasive species is well known for excreting honeydew containing detectable DNA. Worker ants were collected from SLF-infested and non-infested sites and analysed using endpoint PCR and quantitative PCR (qPCR, TaqMan assay) to detect SLF DNA. Both assays successfully detected SLF DNA in 60–100% of ant samples from infested sites, while no SLF DNA was found in ants from non-infested locations. Compared to non-ant insects, ants exhibited higher SLF DNA concentrations, suggesting that honeydew ingestion serves as the primary eDNA source. These findings demonstrate that ants can function as efficient SLF eDNA samplers, providing a scalable and cost-effective alternative to existing SLF detection methods.